2019
DOI: 10.3390/app9112247
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect Mechanism of MRD to Rotor System

Abstract: Magnetorheological damper (MRD), a semi-active control device, has the stability of the passive control device and the adaptive ability of the active control device. It is considered to be an ideal replacement for the squeeze film damper (SFD) and has been extensively investigated. However, the effect mechanism of MRD to a rotor system is still unclear, which will influence the structural design and control strategy of MRD. This paper aims to propose a general MRD excitation model for a rotor system and discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…[ 56 ] This effect leads to an increase in base vibration amplitude with the increase in current supply. [ 57 ] The tendency of the clumping effect is observed at near resonance after 0.6 A for Sample 2, as shown in Figure . The results were obtained by testing the vibration attenuations at various currents for MRF sample using the experimental setup, which shows the negative damping effect at a higher current (i.e., clumping effect when vibration amplitude starts to increase).…”
Section: Experimental Results Of System Vibration Using Biodegradable...mentioning
confidence: 87%
See 1 more Smart Citation
“…[ 56 ] This effect leads to an increase in base vibration amplitude with the increase in current supply. [ 57 ] The tendency of the clumping effect is observed at near resonance after 0.6 A for Sample 2, as shown in Figure . The results were obtained by testing the vibration attenuations at various currents for MRF sample using the experimental setup, which shows the negative damping effect at a higher current (i.e., clumping effect when vibration amplitude starts to increase).…”
Section: Experimental Results Of System Vibration Using Biodegradable...mentioning
confidence: 87%
“…Both the results of Sample 2 and Sample 5 are inline with the result of Wang et al 2019. [ 57 ] Therefore, more possibility of vibration amplitude reduction with an increase in current supply may be experienced in Sample 5 rather than in biodegradable oil‐based MRF Samples.…”
Section: Experimental Results Of System Vibration Using Biodegradable...mentioning
confidence: 99%
“…Considering the effect of the cavitation, Ruggiero et al [4] found the "oil whirl" produced by the non-linear fluid forces. Wang [5] studied a controllable SFD for a rotor system and revealed its effect mechanism. Chang [6][7][8] analyzed the dynamic behavior of a hybrid SFD-mounted gear-bearing system based on the typical unbalance approximation and discussed the rotating speed and damping effects.…”
Section: Rotor Systemmentioning
confidence: 99%
“…Chasalevris and Dohnal (2014) proposed a passive adjustable sliding bearing, which can effectively reduce the resonance amplitude of the journal, but the damping frequency band is limited, and most of them are suitable for high-frequency vibration. In terms of designing various dampers (Lu et al, 2019), Forte et al (2004), Wang et al (2019) and Piccirillo et al (2015) studied the vibration reduction effect and strategy of a Mr Fluid damper in a rotor system. Zhu (2001) proposed the magnetorheological fluid SFD that changes the flow form of a magnetic fluid by applying a controllable magnetic field in the oil film region so as to control the dynamic characteristics of the damper and effectively control the overcritical vibration of the rotor.…”
Section: Introductionmentioning
confidence: 99%